Determination of glutathione peroxidase (GSH-Pex) activity in sera & RBCs of Iraqi Women With Breast Tumors (Baghdad Science Journal, 2025)
Breast tumor patients generally have more oxidative stress than normal females. This was clear from non significant decrease in RBCs and serum of GSH-Pex activity in all groups of patients. The study had found that free radicals in malignant breast tumors were higher than benign tumors; therefore the GSH- Pex might be used as markers for prognosis of the disease.